2023
DOI: 10.2147/jir.s401968
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Behavior of Bone Macrophage as Well as Associated Osteoimmunity in Glucocorticoid-Induced Osteonecrosis of the Femoral Head

Abstract: Glucocorticoid-induced osteonecrosis of the femoral head (GIONFH) is a disabling disease with high mortality in China but the detailed molecular and cellular mechanisms remain to be investigated. Macrophages are considered the key cells in osteoimmunology, and the cross-talk between bone macrophages and other cells in the microenvironment is involved in maintaining bone homeostasis. M1 polarized macrophages launch a chronic inflammatory response and secrete a broad spectrum of cytokines (eg, TNF-α, IL-6 and IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 113 publications
(184 reference statements)
0
7
0
Order By: Relevance
“…Dex exerts potent anti-inflammatory effects. It acts on M cells to promote M1 to M2c polarization by inhibiting inflammation signaling pathways, including NF-κB . Additionally, by directly inhibiting TGF-βR1 and Smad3 activity, Dex can decrease M2 cell polarization, reduce probability of MMT cells conversion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dex exerts potent anti-inflammatory effects. It acts on M cells to promote M1 to M2c polarization by inhibiting inflammation signaling pathways, including NF-κB . Additionally, by directly inhibiting TGF-βR1 and Smad3 activity, Dex can decrease M2 cell polarization, reduce probability of MMT cells conversion.…”
Section: Resultsmentioning
confidence: 99%
“…It acts on M cells to promote M1 to M2c polarization by inhibiting inflammation signaling pathways, including NF-κB. 48 Additionally, by directly inhibiting TGF-βR1 and Smad3 activity, 49 Dex can decrease M2 cell polarization, reduce probability of MMT cells conversion. ERS has been shown to play a significant role in renal fibrosis, 50 as evidenced by the high expression of the ER stress-related protein GRP78 observed in the immunofluorescence section of renal tissue isolated from UUO mice (Figure 2A).…”
Section: Inhibition Of Atf6 Assists Glucocorticoids In Reversing M2a ...mentioning
confidence: 99%
“…Previous studies reported that the immune inflammatory response generated by immune cell infiltration involved the disease process of ONFH [32,33]. Therefore, we explored the differences between two m6A subtypes in various immune cells.…”
Section: Investigation Of the Relationship Between Immune Cell Infilt...mentioning
confidence: 98%
“…Then, TRAF6 can activate NF-κB through TGF-β activated kinase 1 (TAK1) and MAPKs, such as JNK, extracellular-signal-regulated kinase (ERK), and p38 kinase, through mitogen-activated protein kinase ERKA 6 (MKK6), which, in turn, activates AP-1, leading to the expression of proinflammatory cytokines ( 51 , 85 87 ). Several different inflammatory cytokines, including TNF-α, IL-6, and IL-1β, are induced through this signaling pathway ( 88 ). For example, retinol-binding protein 4 (RBP4) contributes to insulin resistance and heart failure by activating the TLR4/MyD88 signaling pathway ( 49 ).…”
Section: Toll-like Receptors Are Associated With Cardiac Hypertrophymentioning
confidence: 99%